Daya Terima dan Nilai Gizi MP-ASI Berbahan Pangan Lokal Sebagai Upaya Mencegah Stunting Anak Baduta - Rabiatul Aulia; Nany Suryani; Norhasanah; Siti Aisyah Solechah (Universitas Muhammadiyah Surakarta, 2023)
Introduction: Stunting is a condition of failure to thrive in children due to cronic nutritional deficiencies from inadequate complementary feeding. Local food is commonly consumed by local people in accordance with the condition of the potential resources and local wisdom of the area. The purposes this study to determine the acceptability and nutritional value (energy, protein, fat, carbohydrates, vitamin C, vitamin D, vitamin A, calcium, iron, and zinc) of complementary feeding made from local food. Method: The type of research was an experimental by making 15 recipes complementary feeding. The nutritional value was tested using the software nutrisurvey 2007 and TKPI 2017 and the acceptability was assessed using the food weighing method on 90 panelist. Results: Complementary feeding with good acceptability were Tilapia Potato Porridge (6-8 months), Purple Sweet Potato Shepherd Pie (9-11 months), and Striped Snakehead Purple Sweet Potato Cakes (12-23 months). The complementary feeding menus in this study were able to meet the RDA (energy, protein, fat, carbohydrate, vitamin C, calcium, and zinc) but breats milk and snack still had to be given to under-two children. Conclusion: Children under-two years old tend to like snack-like foods and sweet-flavored complementary feeding.